2017
DOI: 10.3390/coatings7020027
|View full text |Cite
|
Sign up to set email alerts
|

Coating Qualities Deposited Using Three Different Thermal Spray Technologies in Relation with Temperatures and Velocities of Spray Droplets

Abstract: Abstract:Three guns based on different thermal spray technologies-namely, gas flame spray, wire arc spray, and wire plasma spray-were operated at each best cost-performance condition, and the resulting spray droplets and deposited coating qualities were investigated. For the former, a simple optical monitoring system was used to measure temperatures and velocities of spray droplets ejected from the guns. On the other hand, for the latter, qualities of coating layers on substrates-namely, surface roughness, ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 7 publications
1
18
1
Order By: Relevance
“…The impact of these particles allows them to deform and form on the topography of the substrate before the solidification of a denser coating, with greater union between splats and the growth of a less porous structure. Similar results were reported by Y. Kawaguchi [15], who indicated that high porosity is due to a low velocity of the drops, resulting from their poor acceleration by the compressed air during the thermal spraying. Figure 8 shows the potentiodynamic polarization curves for the coatings deposited at various working pressures.…”
Section: Microstructural Characterization Of Al-cu-fe Coatingssupporting
confidence: 89%
“…The impact of these particles allows them to deform and form on the topography of the substrate before the solidification of a denser coating, with greater union between splats and the growth of a less porous structure. Similar results were reported by Y. Kawaguchi [15], who indicated that high porosity is due to a low velocity of the drops, resulting from their poor acceleration by the compressed air during the thermal spraying. Figure 8 shows the potentiodynamic polarization curves for the coatings deposited at various working pressures.…”
Section: Microstructural Characterization Of Al-cu-fe Coatingssupporting
confidence: 89%
“…Likewise, microcracks, similar to pores, can induce macroscopic failures when a sufficiently high load is applied. It was also observed that small cracks around the scratch path may decrease cohesive resistance in the test [18,33]. In the present investigation, a direct relationship between porosity and resistance to cohesion was not found, probably because hardness had a more important effect, due to the fact that it was an abrasion test.…”
Section: Resultscontrasting
confidence: 62%
“…The impact of these particles allows their deformation on the topography of substrate before its solidification, which produces a denser coating with greater bonding between splats and a less porous structure. Kawaguchi [33] indicates that the high porosity is due to the low velocity of the drops resulting from its poor acceleration by compressed air in the thermal projection process. Figure 4a shows the results of the microhardness vs. the particle collision speeds.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the high process temperature of these techniques, the thermal-sprayed coatings inevitably have problems such as oxidation, phase transition, porosity and residual thermal stresses. For example, the porosity of arc spraying and flame spraying is generally higher than 10%, while plasma spraying and HVOF technologies usually results in 3-8% and <3% porosity, respectively [21,22]. Consequently, the quality of coatings is degraded due to the high porosity [23,24].…”
Section: Introductionmentioning
confidence: 99%